Peculiarities of Acromioplasty in Patients with Chronic Massive Rotator Cuff Ruptures - Strafun, S.S.; Bohdan, S.V.; Yuriichuk, L.M.; Strafun, O.S.; Biliavskyi, V.O. (TERRA ORTHOPAEDICA, 2023)
Background. According to the literature, from 14% to 28% of patients with rotator cuff tendon ruptures have unsatisfactory results of treatment and require a reverse shoulder joint arthroplasty in the future. Objective: to compare the results of open rotator cuff repair of chronic massive rotator cuff tears in groups with standard subacromial decompression and subacromial decompression with resection of the lateral part of the acromion. Materials and Methods. The study included 58 patients who underwent an open rotator cuff repair of chronic massive rotator cuff tears (supraspinatus and infraspinatus tendons) and who underwent a rehabilitation program and follow-up up to 12 months after surgery. The age of the patients ranged from 30 to 60 years. All patients were divided into 2 groups: group 1 – classic subacromial decompression, group 2 – classic subacromial decompression complemented by resection of 5 mm of the lateral end of the acromion. Shoulder joint function was assessed using the Constant Shoulder Score and VAS scales before surgery, 6 and 12 months after surgery. Results. Six months after surgery, the mean functional result on the Constant Shoulder Score scale in group 1 was slightly worse (24.5 ± 16.2 points) than in group 2 (18.5 ± 6.1 points); p = 0.131. Twelve months after surgery, the mean functional score on the Constant Shoulder Score was 21.1 ± 5.6 points in group 1 and 10.1 ± 6.1 points in group 2 (p = 0.031). Six months after surgery, the average score on the VAS scale was worse in group 1 than in group 2 and ranged from 3.5 ± 1.2 points. Twelve months after surgery, the mean score on the VAS scale was also worse in group 1 than in group 2 (p = 0.05). Conclusions. Resection of the lateral part of the acromion during the open rotator cuff repair of chronic massive rotator cuff tendons tears allows to obtain better average functional results of treatment both 6 months and 12 months after the surgery. Resection of the lateral end of the acromion changes the vector of the total force of the rotator cuff and deltoid muscles during shoulder elevation. This reduces the probability of the subacromial conflict syndrome development and thus reduces the load on the area of the rotator cuff tendon suture.